6-Phosphogluconolactonase Promotes Hepatocellular Carcinogenesis by Activating Pentose Phosphate Pathway - Li, Changzheng; Chen, Jie; Li, Yishan; Wu, Binghuo; Ye, Zhitao; Tian, Xiaobin; Wei, Yan; Hao, Zechen; Pan, Yuan; Zhou, Hongli; Yang, Keyue; Fu, Zhiqiang; et al. (Frontiers in Cell and Developmental Biology, 2021)
Hepatocellular carcinoma (HCC) has a poor prognosis due to its rapid development and early metastasis. HCC goes through a series of metabolic reprogramming to meet the demand of rapid proliferation, but how metabolic reprogramming regulates HCC proliferation remains unclear. Here, by analyzing the single-cell sequencing data of the livers of HCC patients and healthy people, we found that 6-Phosphogluconolactonase (PGLS) positive HCC subtype had the differentiate ability. A stage-dependent increase of PGLS in human liver tumors was correlated with poor prognosis in patients with HCC. We further demonstrated that downregulation of PGLS impaired the proliferation, migration and invasion capacity of HCC. Mechanistically, PGLS maintained low ROS level and inhibited ROS-mediated apoptosis to further promote HCC function. Overall, our study reveals PGLS is a key metabolic reprogramming gene for HCC, providing a potential therapeutic strategy for the treatment of HCC.